EKSPLORASI HIDROKARBON DENGAN METODE GEOLISTRIK KONFIGURASI SCHLUMBERGER DAN KONSEP ANISOTROPI, LAPANGAN RA, WILAYAH BENAKAT BARAT, KECAMATAN BENAKAT, KABUPATEN MUARA ENIM, SUMATERA SELATAN - Rio Andryantoro; Wahju Krisna Hidajat; Dian Agus Widiarso; F.X. Yudi Triyono (Program Studi Teknik Geologi, Fakultas Teknik, Universitas Diponegoro, 2014)
Oil and gas energy still being a high priority industry to support economic of Indonesia, either as source of national income and supply the local energy demands. Development of oil productions decreasing year-by-year, so that, new resources and advance production need to be processed immediately. Oil and gas resources in Indonesia still have a high potential to be developed, one of the high-potential location is Sumatera Island. Tectonic processes made the Tertiary-sedimentary basins in the back of volcanics arc (back arc basin) or in the eastern of Barisan Mountains. South Sumatera Basin was one of those sedimentary basin. Research area located in West Benakat, District of Muara Enim.Among various methods of oil and gas explorations, geoelectric method was chose for th research. This method is relatively simple and inexpensive in cost. Exploration was committed with geoelectric-Schlumberger configuration. Analysis processed with anistopy concept. Area of geoelectric measurements located in RA Field, Benakat Barat Area, South Sumatera. The length was various for each line depends on total of measurement stations. The distance between each measurement station is 100 meters with measurements extend 1000 meters in length for each station. Lines which analyzed in this research were line B, D, and J with 53 measurement stations in total, 20 in line B, 17 in line D, and 16 in line J. Data calculation processed with Microsoft Excel until value of medium resistivity acquired. After that, result from calculation processes will be used for 2D modelling using Surfer 8.Based on data calculation and 2D modelling, three hydrocarbon procpect horizons have been interpreted, they are Horizon H1 in depth between 255 – 287 meters with medium resisitivity 0,87 – 6,27 Ohm meter, Horizon H2 in depth between 462 – 483 meters with medium resistivity 2,62 – 11,58 Ohm meter, and Horizon H3 in depth between 595 – 615 meters with medium resistivity 3,04 – 16 Ohm meter.